2015
DOI: 10.1039/c4cp05389c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic diffusion anomaly at the Néel temperature of pyrrhotite, Fe1−xS

Abstract: Cation diffusion is an important rate-limiting process in the growth of pyrrhotite (Fe1-xS) in passivating films on steels exposed to sulfidic environments, and for proposed synthetic applications of Fe1-xS, for example single-phase magnetic switching devices. Above the Néel temperature TN of 315 °C, where Fe1-xS is paramagnetic and structurally disordered, iron self-diffusivity *DFe predictably follows a standard, established Arrhenius law with temperature. However, we report (57)Fe tracer diffusion measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Interestingly, morphologies of iron metals are different between iron sulfides and magnetite. The self-diffusion coefficient of iron in magnetite 30 is several orders of magnitudes lower than in iron sulfides 31 through a wide range of temperature and oxygen fugacity. Iron nano-particles on magnetite may nucleate from excess iron atoms in the vicinity, while iron whiskers may be derived from excess iron atoms that diffuse long distance to the limited nucleation sites on iron sulfides, perhaps via accelerated surface and/or grain boundary diffusion.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, morphologies of iron metals are different between iron sulfides and magnetite. The self-diffusion coefficient of iron in magnetite 30 is several orders of magnitudes lower than in iron sulfides 31 through a wide range of temperature and oxygen fugacity. Iron nano-particles on magnetite may nucleate from excess iron atoms in the vicinity, while iron whiskers may be derived from excess iron atoms that diffuse long distance to the limited nucleation sites on iron sulfides, perhaps via accelerated surface and/or grain boundary diffusion.…”
Section: Discussionmentioning
confidence: 91%
“…SEM/EDS shows that the outer layer is only FeS, while the inner-layer granules are a mixture of oxides and sulfides (Figure f). Prior research has found that the corrosion proceeds on the outer surface of the inner layer rather than the interface between the steel and the inner layer. Compared with the corrosion on the steel surface, the reactions of the acid or reactive sulfur compounds on the outer surface of the inner layer have to overcome a higher energy barrier (i.e., higher activation energy), resulting in a lower corrosion rate. For the reactions to occur, iron has to diffuse through the inner layer; the presence of oxide in the inner layer formed by the DDS + TCI mixture slows the solid-state diffusion rate.…”
Section: Resultsmentioning
confidence: 99%
“…The iron diffusivity in pyrrhotite may be calculated by eq . In the current study, the adopted value of diffusion activation energy (Δ H Fe in FeS ) is 82 kJ/mol when temperature is above the Néel temperature of pyrrhotite (316 °C) . It is known that the pre-exponential factor D 0,Fe in FeS is a function of crystal orientation with the average value 2 × 10 –6 m 2 /s for random orientation as expected for the inner scale .…”
Section: Modeling Approachmentioning
confidence: 90%
“…Hypothesis 2 is an intuitive extension of oxidation and sulfidation at temperatures well above 400 °C where solid state diffusion of iron through an inner scale is fast . Radiotracer and magnetokinetic measurements over the past 70 years has established that the high-temperature sulfidation of steel proceeds by the outward diffusion of iron through the compact iron sulfide scale by exchange between an iron atom and the neighboring vacancy. Gas phase sulfidation has been proven to proceed by charge transfer with incorporation of sulfur atoms into the iron sulfide lattice and creation of charged iron vacancies (reactions –). Continuous sulfidation results in an iron-deficient outer surface of the inner scale and promotes the solid state diffusion of iron. …”
Section: Introductionmentioning
confidence: 99%